Sport Management Capacity Provincial Board of Sports - Filli Azandi; Sihombing, Hardodi; Harahap, Bahder Johan (Sekolah Tinggi Olahraga & Kesehatan Bina Guna, 2022)
This study aims to determine the improvement of sports management capabilities in North Sumatra in 2020. This research method is a descriptive method. The number of samples was 34 people with sampling techniques with purposive sampling techniques. The research instrument is a questionnaire with data analysis techniques by comparing the two pree test averages = 78 (medium), and the post-test average = 84.5 (good). The results of this study indicate that there is a significant increase in the capacity of the management ability of provincial sports administrators in North Sumatra in 2020. There is a significant increase in the sports management capacity of the provincial board of sports branches in North Sumatra in 2020. It is recommended that the leader of a sports organization has the ability to lead a sports organization determined by the managerial skills possessed, among others; ability to lead, ability to foster, ability to organize, and financial management skills.